The Effect of Internal Control System and Transparency on the Income Growth of IDX-Listed Cigarette Companies - Nadila, Anggi; Aisyah, Siti (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This research aims to determine the effect of Internal Control System and transparency in increasing the income of cigarette sub-sector companies listed on the Indonesian Stock Exchange for the 2015-2021 period. The data source used in this research uses secondary data sources. The type of research used in this research uses quantitative research. The number of samples used in this research was 35 samples. The data analysis technique used in this research uses descriptive statistical analysis, classical assumption testing, multiple linear regression testing and hypothesis testing. The results of this research show that the Internal Control System variable has no significant effect on company income, while the transparency variable has a significant effect on company income. Simultaneously, the Internal Control System and transparency variables have a significant effect on company revenues in the cigarette sub-sector for the 2015-2021 period. As implications, companies in the cigarette sub-sector may benefit from adopting an integrated approach that combines robust internal control systems with a commitment to transparency to maximize their financial performance